1997
DOI: 10.1074/jbc.272.3.1718
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Self-association Sites in Type III Modules of Fibronectin

Abstract: In an effort to detect interactions between other Fn domains, all fragments were coupled to Sepharose, and each fragment was tested on each affinity matrix before and after denaturation. The only interaction detected was that of fluid phase III 1 with immobilized denatured 110-kDa CBF and 40-kDa Hep-2, both of which contain type III domains. Analysis of subfragments revealed this activity to be dominated by domains III 7 and III 15 . Fn itself did not bind to the denatured fragments. Thus, domain III 1 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
96
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 48 publications
(82 reference statements)
2
96
0
1
Order By: Relevance
“…Cryptic sites have been specifically proposed to exist in FN-III 1 , FN-III [7][8] , and FN-III 10 (11). Although our SMD simulations suggest that FN-III 7 is relatively stable, the cryptic site in the FN-III 7-8 dimer could be located at the interface between the two modules (12), implying that prestretching of FN-III 8 into the aligned state exposes the interface between the modules. Other researchers have suggested that FN-III 10 contains a cryptic site that binds to FN-III 1 when FN-III 10 is denatured (7,39).…”
Section: Analysis Of First Passage Times and Energy Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptic sites have been specifically proposed to exist in FN-III 1 , FN-III [7][8] , and FN-III 10 (11). Although our SMD simulations suggest that FN-III 7 is relatively stable, the cryptic site in the FN-III 7-8 dimer could be located at the interface between the two modules (12), implying that prestretching of FN-III 8 into the aligned state exposes the interface between the modules. Other researchers have suggested that FN-III 10 contains a cryptic site that binds to FN-III 1 when FN-III 10 is denatured (7,39).…”
Section: Analysis Of First Passage Times and Energy Barriersmentioning
confidence: 99%
“…Forced unfolding of the FN-III 10 module also has been suggested to modify exposure of the RGD loop, thus influencing FNЈs accessibility to integrins (9). Mechanical forces, furthermore, are essential in initiating FN fibril assembly (10), potentially through exposure of cryptic sites, and͞or by swapping complementary ␤-strands of partially unfolded FN-III modules during refolding (11,12). The functional states of FN are tightly regulated because FN is central in mediating and regulating cell adhesion, proliferation, and migration through various integrindependent signaling pathways (5).…”
mentioning
confidence: 99%
“…There are at least three mechanisms by which hyperextension of Fn can alter its functional states: (i) by exposing cryptic sites that are buried between Fn modules in the native state; (ii) by changing the relative distance of two or more binding sites that bind the same receptor; and (iii) by straightening the hydrophilic loops that carry binding sites (30). Cryptic sites have been identified on FnIII 1 , FnIII [7][8] , and FnIII 10 that must be exposed to initiate Fn matrix assembly (31)(32)(33)(34) (35). This reduction in integrin affinity is caused by an increase in the distance between the arginine-glycine-aspartic acid (RGD) loop and its synergy site, from 3.2 nm to 5.6 nm.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33][34] Moreover, the exposure of cryptic sites in Fn modules is an important event regulating integrin binding, cell signaling and the ability of cells to construct new matrix fibrils. 30,[35][36][37] Conversely, changes in cell contractility have been shown to alter access to these same sites within matrix fibrils. Inhibition of Rho A, an agonist of cell contractility, prevents the exposure of a cryptic site in FnIII 1 , and disruption of the actin cytoskeleton with cytochalasin D causes refolding of Fn type III modules in fibrils assembled between cells and an underlying glass substrate.…”
Section: Introductionmentioning
confidence: 99%